Pemberdayaan Masyarakat Untuk Meningkatkan Kualitas Hidup - Pradana, Dimas Shakti; Damayanti, Dita Tristanti; Widyasari, Dyah Rahayu; Aryanti, Effie Dwi; Aryani, Eka Yeni; Terani, Eldiana; Yuliana, Yomimma Vienna (Jurnal Pemberdayaan: Publikasi Hasil Pengabdian Kepada Masyarakat, 2024)
This Thematic Real Work Lecture activity focuses on community empowerment to improve the quality of life for children at the Aisha Jena Orphanage Foundation in the hope of increasing knowledge and improving the quality of life for children. This Thematic Real Work Lecture activity aims to provide socialization and education about mental health and the impact of bullying. Parents certainly have an important role in building children's development, therefore the target in this Thematic Real Work Lecture activity is the creation of success in fostering reasoning power, a sense of responsibility, empathy, and adding direct learning experiences, and applying them in everyday life in society. The method in this Thematic Real Work Lecture activity is in the form of socialization about understanding reasoning power, a sense of responsibility and providing direct education, because not all children in the orphanage know material about mental health and the impact of bullying in order to prevent bullying cases from increasing.